Marketing communication strategy for merchants in The SP market - Elva Susanti; Ance Jusmaya; Citra Indah Asmarawati; Rizki Prakasa Hasibuan (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
In communicating, speaking with the public requires sense, how we speak well, with our speech it will provide special data for the listener, the ability to liven up the atmosphere will be good if we have good communication skills. So that the objectives that we will convey will be achieved. Thus, both traders, consumers, or anyone else need to be given knowledge of efficient communication methods. In this case, the lecturer provides communication and marketing strategies, sales promotions, and public relations to the community around the market.